2021
DOI: 10.3389/fphys.2021.729123
|View full text |Cite
|
Sign up to set email alerts
|

Spleen Contraction During Sudden Eupneic Hypoxia Elevates Hemoglobin Concentration

Abstract: The spleen contracts progressively during moderate normobaric hypoxia exposure of 20 min, which elevates hemoglobin concentration (Hb). However, acute hypoxia exposure could be shorter and more severe when oxygen systems fail during, e.g., high-altitude sky diving, aircraft cabin pressure drop, balloon flights, extreme altitude climbing, and in some maladies. We aimed to evaluate the speed and magnitude of spleen contraction during short exposure to extreme eupneic hypoxia and its subsequent recovery on oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…Additionally, the aforementioned studies have mostly focused on autonomic and cardiovascular responses, thus excluding other organs that could contribute to the maintenance of oxygen saturation despite not experiencing ventilation. One of these organs could be the spleen, which has been shown to play an important role in the responses and adaptations to hypoxic training; however, studies of this organ in voluntary apnea conditions are extremely limited ( Engan et al, 2013 ; Pernett et al, 2021 ).…”
Section: Central and Peripheral Interaction: A Key Point In Autonomic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the aforementioned studies have mostly focused on autonomic and cardiovascular responses, thus excluding other organs that could contribute to the maintenance of oxygen saturation despite not experiencing ventilation. One of these organs could be the spleen, which has been shown to play an important role in the responses and adaptations to hypoxic training; however, studies of this organ in voluntary apnea conditions are extremely limited ( Engan et al, 2013 ; Pernett et al, 2021 ).…”
Section: Central and Peripheral Interaction: A Key Point In Autonomic...mentioning
confidence: 99%
“…This reservoir of blood, which is delivered into the systemic circulation, is capable of contributing to maintaining oxygen saturation for a long time period, despite not experiencing pulmonary ventilation ( Bakovic et al, 2003 ; Richardson et al, 2008 ). Additionally, it can maintain hemoglobin levels during prolonged voluntary apnea or short-term exposure to eupneic normobaric hypoxia ( Bakovic et al, 2003 ; Richardson et al, 2008 ; Lodin-Sundström and Schagatay, 2010 ; Pernett et al, 2021 ). The blood contained in the spleen is released into the systemic circulation via splenic contraction, which is dependent on sympathetic activity ( Bakovic et al, 2013 ).…”
Section: Spleen-chemoreflex Relationship In Voluntary Apneamentioning
confidence: 99%
“…Previous studies have found effects from chemoreceptor stimulation on splenic contraction and associated hematological changes ( Pernett et al, 2021 ). Lodin-Sundström and Schagatay (2010) showed that apnea induced a significantly more pronounced splenic contraction than normobaric hypoxic breathing, at similar hypoxic stress, and suggested that hypercapnia or a faster development of hypoxia during apnea might explain the difference.…”
Section: Discussionmentioning
confidence: 99%
“…The splenic contraction is most likely related to an increase in sympathetic nervous activity, with the splenic nerve containing approximately 98% sympathetic nerve fibers ( Felten et al, 1985 ; Mignini et al, 2003 ). Splenic contraction can also be initiated by various other stressors associated with an increase in sympathetic activity ( Shephard, 2016 ), such as exercise ( Laub et al, 1993 ; Engan et al, 2014 ), normobaric hypoxic breathing ( Richardson et al, 2008 ; Pernett et al, 2021 ), and high-altitude exposure ( Schagatay et al, 2020 ; Holmström et al, 2021 ). The observations with normobaric hypoxic breathing and high-altitude exposure suggest that hypoxia could be a key stimulus for splenic contraction.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies of splenic and haematological reactions after apnoea have already been performed in the literature (Shephard et al, 2016;Elia et al, 2021;Pernett et al, 2021;Nordine et al, 2022). It has been proven that long-term static apnoea training increases both spleen volume and HGB (Bouten et al, 2019).…”
Section: Introductionmentioning
confidence: 99%